Cooling forests, calmer hearts: Urban forest structure, microclimate and heat relief in adolescents - Sophie Feiertag; Daniel A. Scheller; Jan Schmid-Ellinger; Anna-Katharina Eisen; Filip Mess; Annette Menzel (Urban Forestry & Urban Greening, 2026)

Potential factors contributing to observed sex differences in virtual-reality-induced sickness - Grainne M. Bannigan; Alexandra A. de Sousa; Meike Scheller; Daniel J. Finnegan; Michael J. Proulx (Experimental Brain Research, 2024)
Virtual reality (VR) technology has been widely adopted for several professional and recreational applications. Despite rapid innovation in hardware and software, one of the long prevailing issues for end users of VR is the experience of VR sickness. Females experience stronger VR sickness compared to males, and previous research has linked susceptibility to VR sickness to the menstrual cycle (Munafo et al., Exp Brain Res 235(3):889–901). Here we investigated the female versus male experience in VR sickness while playing an immersive VR game, comparing days of the menstrual cycle when hormones peak: day 15 (ovulation—peak estrogen) and day 22 (mid-luteal phase—peak progesterone). We found that immersion duration was greater in the second session than the first, and discomfort was lessened, suggesting a powerful adaptation with repeated exposure. Due to the estrogen levels changing along with the exposure, there was no clear independent impact of that; note, though, that there was a significant difference between self-report and physiological measures implying that GSR is potentially an unreliable measure of motion sickness. Although prior work found a delay over 2 days between session would not allow adaptation and habituation to reduce VR sickness susceptibility, we found that a week delay has potential success.